Estimation of a transformation model with truncation, interval observation and time-varying covariates - Bo E. Honoré; Luojia Hu (Federal Reserve Bank of Chicago, 2009)
Abrevaya (1999b) considered estimation of a transformation model in the presence of left-truncation. This paper observes that a cross-sectional version of the statistical model considered in Frederiksen, Honoré, and Hu (2007) is a generalization of the model considered by Abrevaya (1999b) and the generalized model can be estimated by a pairwise comparison version of one of the estimators in Frederiksen, Honoré, and Hu (2007). Specifically, our generalization will allow for discretized observations of the dependent variable and for piecewise constant timevarying explanatory variables.
Keywords: 330